Gerakan Kultural dan Pemberdayaan: Sebuah Imun atas Radikalisasi di Sanggar Sekar Jagad di Sukoharjo - A. Jauhar Fuad (IAIN Ponorogo, 2018)
Abstract: This paper aims to explain the prevention of radicalization through cultural movement and empowerment. This approach is done by art that is believed to be able to stem the streams that conflict with the Republic of Indonesia, the 1945 Constitution and Pancasila. By art in addition to preserving Javanese traditions, but far behind all that, cultivating a sense of nationalism, as well as patriot souls in the nation's children. Sanggar as a place of art builds its community through three important components; (1) community organizing in the form of studio, (2) art performances or performing arts, (3) strengthening the economic sector through assistance and empowerment of rural communities. Art galleries are handling radicalization that is rooted from below, ie a shared consciousness that grows from the idea of a 'bottom up' society. On the other hand to empower the community in a variety of assistance activities in various sectors of life in the form of activities. For example: training and workshops in the field of Small and Medium Enterprises, agriculture, animal husbandry, fisheries, plantation and entrepreneurship. This move can counteract and stem the flow of radicalism that enters the countryside.الملخص: تهدف هذه الورقة إلى شرح الوقاية من التطرف من خلال الحركة الثقافية والتمكين. ويتم هذا النهج بفن يُعتقد أنه قادر على وقف التدفقات التي تتعارض مع جمهورية إندونيسيا ودستور عام 1945 وبنكاسيلا. من خلال الفن بالإضافة إلى الحفاظ على التقاليد الجاوية ، ولكن وراء كل ذلك ، زراعة الشعور بالقومية ، فضلا عن الروح الوطنية في أبناء الأمة. يبني سنجار كمكان فني مجتمعه من خلال ثلاثة مكونات مهمة ؛ (1) تنظيم المجتمع في شكل استوديو ، (2) العروض الفنية أو الفنون الأدائية ، (3) تعزيز القطاع الاقتصادي من خلال المساعدة وتمكين المجتمعات الريفية. تعالج المعارض الفنية التطرف المتجذر من أسفل ، أي الوعي المشترك الذي ينمو من فكرة مجتمع